Global Database on Nominal Rate of Assistance (NRA) 2023 - AgIncentives Consortium (International Food Policy Research Institute, 2023)
The Consortium's Nominal Rate of Assistance (NRA) dataset contains a set of measures of the incentives that affect producers' decision making in agricultural sector. These measures are categorized by their potential economic impacts, with market price support distinguished from payments based on output; payments based on inputs; and payments based on other indicators, such as factors of production, current or past area or livestock numbers.